2002
DOI: 10.1093/jn/132.8.2235
|View full text |Cite
|
Sign up to set email alerts
|

Dietary (n-3) Polyunsaturated Fatty Acids Up-Regulate Plasma Leptin in Insulin-Resistant Rats

Abstract: The study was designed to evaluate the chronic regulation of plasma leptin by dietary (n-3) polyunsaturated fatty acids (PUFA) in insulin-resistant, sucrose-fed rats. Male Sprague-Dawley rats were randomly assigned to consume for 3 or 6 wk a diet containing 57.5% (g/100 g) sucrose and 14% lipids as either fish oil (SF) or control oils (SC). After 3 and 6 wk of consuming the SF diet, plasma leptin was 70% (P < 0.001) and 75% (P < 0.05) greater, respectively, than in rats fed the SC diet. The same result was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 26 publications
7
45
1
2
Order By: Relevance
“…A dietary intake of fish oil or 22:6n-3 has been shown to influence plasma insulin and adipocytokine levels (Flachs et al, 2006;Peyron-Caso et al, 2002;Perez-Matute et al, 2005;Neschen et al, 2006;Miura et al, 1997;Steerenberg et al, 2002). In the present study, an intake of fish oil also significantly increased insulin, leptin, and adiponectin levels but not resistin when compared with the lard diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A dietary intake of fish oil or 22:6n-3 has been shown to influence plasma insulin and adipocytokine levels (Flachs et al, 2006;Peyron-Caso et al, 2002;Perez-Matute et al, 2005;Neschen et al, 2006;Miura et al, 1997;Steerenberg et al, 2002). In the present study, an intake of fish oil also significantly increased insulin, leptin, and adiponectin levels but not resistin when compared with the lard diet.…”
Section: Discussionmentioning
confidence: 99%
“…At any rate, these changes of fatty acid composition may influence the secretion of insulin and adipocytokines. Some reports have suggested that an intake of 20:5n-3 and 22:6n-3 activates the expression of leptin and adiponectin mRNAs (Flachs et al, 2006;Peyron-Caso et al, 2002;Perez-Matute et al, 2005;Neschen et al, 2006) and that 20:4n-6 enhances the expression of resistin mRNA (Haugen et al, 2005). Thus, in this study, it is conceivable that plasma adipocytokine levels are related to the differences in the levels of 20:5n-3, 22:6n-3, and 20:4n-6 in plasma and liver from animals on the kazunoko lipid and fish oil diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature indicates that n-6 PUFA do not alter leptin whereas n-3 PUFA exert variable results (Takahashi and Ide, 2000;Reseland et al, 2001;Korotkova et al, 2002;Peyron-Caso et al, 2002). Insulin stimulates leptin production and secretion (Havel, 2002).…”
Section: Dietary Fatty Acids and Pcos S Kalgaonkar Et Almentioning
confidence: 99%
“…Peyron-Caso and colleagues reported that omega-3 fatty acids upregulate plasma leptin levels in insulinresistant rats by 70% after three weeks of fish oil and 75% after six weeks [52] . Subsequently, an affiliated group demonstrated that omega-3 fatty acids were able to reverse the inhibitory effect of a long-term sucroserich diet on serum leptin levels in insulin-resistant rats [53] .…”
Section: Leptinmentioning
confidence: 99%